Determination of triglycerides storage in hep-G2 cells supplemented with exogenous lipids and stevia extract - Azilyana Fadzli (2019)
Stevia is a sweet herb that acts as a sugar substitute extracted from Stevia sp.( Stevia rebaudiana Bertoni ) that is safe to be consumed. For patients with low tolerance to cholesterol-lowering statins, natural remedies like stevia may be a used as an alternative cholesterol-lowering medication . It was widely used not only as alternative for sugar due to the presence of non-caloric sweetener - stevioside but also as a form of cholesterol-reducing treatment to prevent heart diseases. The aim of this study is to determine the anti-triglyceride effect of commercial Stevia extracts by quantifying the amount of neutral lipids internalization inside the HepG2 cells. The amount of lipid was quantified by using lipid extraction method adopted from Bligh and Dyer lipid extraction protocol. Besides, the amount of lipid internalization was observed through immunofluorescent staining microscopy. Results shows that cells supplemented with exogenous lipid and commercial stevia extracts increased in the amount of lipid droplets stored in cells. Therefore, this suggests that stevia has potential value as anti-triglyceride and anti-cholesterol effects as it has almost similar effects to simvastatin drug.
Project paper (D.V.M) - Universiti Putra Malaysia, 2019.